STABILITY INDICATING UV SPECTROPHOTOMETRIC METHOD FOR DETERMINATION OF DRONEDARONE HYDROCHLORIDE (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The objective of this study was to develop stability UV method for estimation of Dronedarone Hydrochloride in tablet to compare % degradation of this drug determined by this UV method to HPTLC method reported by us earlier. Analysis of bulk as well as marketed tablet formulation by exposure to same degradative conditions was done and % degradation obtained by spectroscopy was determined. Method development and validation was done as per ICH guidelines. % degradation observed by both methods was comparable. The variation in the results of this drug estimated by HPTLC and spectrophotometric method was statistically insignificant. This suggests that the spectrophotometric method is suitable to determine stability profile. Hence a simple UV spectrophotometry can be used to monitor stability of Dronedarone Hydrochloride.